Penguatan Efikasi Diri bagi Guru SMK Sasmita Jaya 2 - Rusmaini, Rusmaini; Zubaidah , Siti; Anwar, Saiful (Universitas Pamulang, 2024)
This PkM is an implementation of research previously conducted by the PkM team entitled Factors that influence Professional Commitment. There are three dimensions that can explain self-efficacy, namely (a) the Magnitude dimension (level of interest in the task), (b) the Strength dimension (steadiness of beliefs), and (c) the Generality dimension (breadth of Behavioral Field). A person who has high self-efficacy will make teachers have more self-confidence that they are able to carry out the tasks they carry out, where in the end, high teacher self-efficacy will of course be able to increase professional commitment and have an impact on improving the performance of Sasmita Jaya Vocational School teachers. 2. This PKM is present at SMK Sasmita Jaya 2 in order to provide reinforcement to teachers at SMK Sasmita Jaya 2 about self-efficacy and how self-efficacy can improve the performance of SMK teachers themselves. This PKM is planned to be implemented in the form of a workshop over three days, namely 18 to 20 March 2024 with the main resource person being Mrs. Siti Zubaidah. The output of this Community Service is in the form of a journal article which will be disseminated at the NC3E national seminar for the Economic Education Study Program in October 2024. Keywords: Self-Efficacy, Teacher